The research was conducted for 12 months at three different locations of poultry farm at Kemang of Parung sub district, Bogor. The sites are about 10 km away from Bogor, surrounded by orchards or other trees and far enough of human dwelling. The influence of ambient temperature, humidity, monthly rainfall and number of rainy days were observed against the population of filth flies Musca domestica and Ophyra chalcogaster. Within a year the four climatic factors during wet and dry seasons were not - F .X. Koesharto; Susi Soviana; Etih Sudarnika (Media Veteriner, 2000)
The research was conducted for 12 months at three different locations of poultry farm at Kemang of Parung sub district, Bogor. The sites are about 10 km away from Bogor, surrounded by orchards or other trees and far enough of human dwelling. The influence of ambient temperature, humidity, monthly rainfall and number of rainy days were observed against the population of filth flies Musca domestica and Ophyra chalcogaster. Within a year the four climatic factors during wet and dry seasons were not significantly different (p>0.05), and the influence of climate was not distinct against the population of filth flies and parasitoid. However, the population of parasitoid was strongly correlated of filth flies (r=0.921).